2019
DOI: 10.1007/s12603-019-1170-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Handgrip Strength and Muscle Mass with Dependency in (Instrumental) Activities of Daily Living in Hospitalized Older Adults -The EMPOWER Study

Abstract: Objectives Handgrip strength (HGS) and muscle mass are strong predictors for dependency in Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) in community dwelling older adults. Whether this also applies to older hospitalized patients is yet unknown. We studied the association between HGS and muscle mass with ADL and IADL dependency at admission and change of ADL and IADL dependency at three months after discharge in older hospitalized patients. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 48 publications
(47 reference statements)
4
20
2
1
Order By: Relevance
“…Loss of muscle mass could be explained by a variety of different factors including the loss of innervation from alpha‐motor neurons , reduced dietary protein intake , and less physical activity . Individuals with lower muscle mass have more difficulty in performing ADL and IADL . Furthermore, it has been suggested that the infiltration of fat into the muscle is a risk factor for low muscle mass, which is associated with worsening ADL and IADL .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of muscle mass could be explained by a variety of different factors including the loss of innervation from alpha‐motor neurons , reduced dietary protein intake , and less physical activity . Individuals with lower muscle mass have more difficulty in performing ADL and IADL . Furthermore, it has been suggested that the infiltration of fat into the muscle is a risk factor for low muscle mass, which is associated with worsening ADL and IADL .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with lower muscle mass have more difficulty in performing ADL and IADL 111,112 . Furthermore, it has been suggested that the infiltration of fat into the muscle is a risk factor for low muscle mass, which is associated with worsening ADL and IADL 111 .…”
Section: Muscle Massmentioning
confidence: 99%
“…En nuestro estudio, la FA de las jóvenes universitarias se encontró por arriba del p50 de acuerdo a la edad y sexo en concordancia con dos referencias con población adulta Latinoamericana 21,22 . Si bien, los resultados de este estudio muestran que la población tenía una adecuada FA, es necesario identificar de forma temprana estos indicadores para así promover el mantenimiento de un estilo de vida saludable por medio de ejercicio físico y dieta saludable, lo que posibilita que las mujeres jóvenes universitarias preserven su masa muscular, fuerza y funcionalidad en esta etapa de la vida 3,27 . De igual manera, los resultados contribuyen a fomentar la FM como indicador de salud en los sistemas de vigilancia epidemiológica, justificándose claramente durante la etapa universitaria debido a que investigaciones en jóvenes universitarias señalan que una baja FM se relaciona con perfiles metabólicos pobres, obesidad, y dolores músculo esqueléticos, mismos que fomentarían resultados poco favorables en salud en su vida posterior 7,28 .…”
Section: Resultsunclassified
“…Low handgrip strength can possibly cause falls or activities of daily living disability 23 . The handgrip strength is known to correlate with the limb muscle strength, which is available for the evaluation of muscle strength 24 .…”
Section: Discussionmentioning
confidence: 99%